ChemInform Abstract: Ene‐Carbonyl Reductive Coupling for the Synthesis of 3, 3‐Disubstituted Phthalide, 3‐Hydroxyisoindolin‐1‐one and 3‐Hydroxyoxindole Derivatives. Issue 35 (2nd September 2014) - Yeh, Chien‐Hung; Lin, Yi‐Chuen; Mannathan, Subramaniyan; Hung, Kevin; Cheng, Chien‐Hong
Abstract Moreover, the intramolecular reductive coupling of ene‐phthalimide (XI) proceeds highly diastereoselective.